2012
DOI: 10.7863/jum.2012.31.5.763
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Diagnostic Value of Acoustic Radiation Force Impulse Technology for Differentiating Between Benign and Malignant Thyroid Nodules

Abstract: Abbreviations ARFI, acoustic radiation force impulse; ROI, region of interest; VTI, Virtual Touch tissue imaging; VTQ, Virtual Touch tissue quantification ORIGINAL RESEARCHObjectives-This study aimed to evaluate the diagnostic value of acoustic radiation force impulse (ARFI) elasticity imaging for differentiating between benign and malignant thyroid lesions.Methods-Hospitalized patients needing thyroid surgery were evaluated. After routine thyroid sonography, the patients underwent ARFI elasticity imaging. Vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 27 publications
8
60
0
4
Order By: Relevance
“…In total, 77.6 % (59 of 76) of the benign nodules showed softer and equal images in the VTI mode, and 77.3 % (17 of 22) of the malignant nodules showed stiffer images (P \ 0.001). They concluded that ARFI imaging has high sensitivity and specificity in evaluating benign and malignant thyroid nodules and therefore a good diagnostic value in clinical applications [16]. More recently, Friedrich-Rust et al [14] compared ARFI and RTE to differentiate benign from malignant thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 77.6 % (59 of 76) of the benign nodules showed softer and equal images in the VTI mode, and 77.3 % (17 of 22) of the malignant nodules showed stiffer images (P \ 0.001). They concluded that ARFI imaging has high sensitivity and specificity in evaluating benign and malignant thyroid nodules and therefore a good diagnostic value in clinical applications [16]. More recently, Friedrich-Rust et al [14] compared ARFI and RTE to differentiate benign from malignant thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Increased reliance on nodule stiffness quantification is therefore needed to bring about a standardization of diagnostic criteria. Acoustic radiation force impulse technology (ARFI), already used in different fields, has also been applied to evaluate diffuse thyroid diseases, [14,15], and recently to differentiate thyroid nodules such as in the study performed by Gu et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…A weak negative correlation calculated in SWE, "X.XX" is displayed on the monitor [10,11]. There are various interpretations of "X.XX" [5,10,[12][13][14][15], with a major view being that "X.XX" represents the SWVs that exceed the range of 1−10 m/s for SWE [5,10,12]. In their study, Bojunga et al substituted numerical values of 8.4 m/s, when "X.XX" was displayed on the monitor [5].…”
Section: Phantom Studymentioning
confidence: 99%
“…Кроме того, необходимы дополнительные исследова-ния для установления пороговых величин эластоме-трии, а также уточнение эластографических параме-тров диагностики субклинических метастазов. Пороговая величина для дифференциальной диагно-стики между непораженными и пораженными опухо-лью лимфатическими узлами, по данным различных исследований, колеблется в пределах 1,5-4,82 м / с [20,[24][25][26][27][28].…”
unclassified